1986
DOI: 10.1007/bf00287583
|View full text |Cite
|
Sign up to set email alerts
|

Gender-role conflict scale: College men's fear of femininity

Abstract: Revised conceptualization and theoretical linkages with child outcomes. In M. E. Lamb (Ed.), The role of the father in child development (5th ed., pp. 58 -93). Hoboken, NJ: Wiley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
1,140
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 665 publications
(1,169 citation statements)
references
References 15 publications
22
1,140
1
6
Order By: Relevance
“…Gender role conflict was measured using the Gender Role Conflict Scale (GRCS; O'Neil et al, 1986), which contains 37 items that measure the cognitive, emotional, and behavioral consequences associated with male gender role socialization. The Between Work and Family Relationships (CBWFR).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gender role conflict was measured using the Gender Role Conflict Scale (GRCS; O'Neil et al, 1986), which contains 37 items that measure the cognitive, emotional, and behavioral consequences associated with male gender role socialization. The Between Work and Family Relationships (CBWFR).…”
Section: Methodsmentioning
confidence: 99%
“…Gender role conflict (GRC; O'Neil et al, 1986), a psychological state in which socialized gender roles contribute to negative interpersonal and intrapsychic consequences, occurs when "rigid, sexist, or restrictive gender roles result in restriction, devaluation, or violation of others or self" (O'Neil et al, 1995, p. 166). Gender role conflict has been conceptualized to have four and Family Relationships (CBWFR).…”
Section: Gender Role Conflictmentioning
confidence: 99%
“…The 16-item GRCS-SF (Wester et al, 2012) is derived from the GRCS (O'Neil, Helms, Gable, David, & Wrightsman, 1986 Wester et al (2012) and summarized in Levant et al (2015), which also found that a hierarchical model best fit the data.…”
Section: Gender Role Conflict Scale-short Form (Grcs-sf)mentioning
confidence: 99%
“…and theorised that heterosexual males would be more defensive in therapeutic settings due to male gender-role conflict (O'Neil et al, 1986). This would also be influenced by a need to avoid behaviours associated with feminine roles such as expressing emotions or affection to other men which are likely to be expected as part of the therapeutic experience (Schaub & Williams, 2007) and likely to be resulting in gender-role conflict and defensiveness to the therapeutic process and therapist.…”
Section: Lgb Therapists Working With Heterosexual Clientsmentioning
confidence: 99%